2004
DOI: 10.1074/jbc.m405317200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Sites of Potential Proximity between the Dihydropyridine Receptor and RyR1 in Muscle Using a Cyan Fluorescent Protein-Yellow Fluorescent Protein Tandem as a Fluorescence Resonance Energy Transfer Probe

Abstract: Excitation-contraction coupling in skeletal muscle involves conformational coupling between the dihydropyridine receptor (DHPR) and the type 1 ryanodine receptor (RyR1) at junctions between the plasma membrane and sarcoplasmic reticulum. In an attempt to find which regions of these proteins are in close proximity to one another, we have constructed a tandem of cyan and yellow fluorescent proteins (CFP and YFP, respectively) linked by a 23-residue spacer, and measured the fluorescence resonance energy transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 42 publications
8
81
1
1
Order By: Relevance
“…Previous work had shown that attachment of either a CFP-YFP tandem (25), or the biotin acceptor domain (26), to a C-terminally truncated ␣ 1S (at residue 1667) did not interfere with function after expression in dysgenic myotubes, and we found similar results for truncation and attachment of YPet at residue 1666 (data not shown). Additionally, we observed that constructs C-terminally tagged with YPet at residue 1666 and N-terminally tagged with CyPet (CyPet-␣ 1S 1666-YPet) produced co-localized cyan and yellow puncta after expression in dysgenic myotubes (Fig.…”
Section: Sites Within ␣ 1s Cytoplasmic Domains Suitable For Labeling supporting
confidence: 86%
See 2 more Smart Citations
“…Previous work had shown that attachment of either a CFP-YFP tandem (25), or the biotin acceptor domain (26), to a C-terminally truncated ␣ 1S (at residue 1667) did not interfere with function after expression in dysgenic myotubes, and we found similar results for truncation and attachment of YPet at residue 1666 (data not shown). Additionally, we observed that constructs C-terminally tagged with YPet at residue 1666 and N-terminally tagged with CyPet (CyPet-␣ 1S 1666-YPet) produced co-localized cyan and yellow puncta after expression in dysgenic myotubes (Fig.…”
Section: Sites Within ␣ 1s Cytoplasmic Domains Suitable For Labeling supporting
confidence: 86%
“…On the basis of these results, all the C-terminally tagged ␣ 1S constructs used for the FRET measurements in this study were truncated at residue 1636. All other ␣ 1S constructs did not have this truncation and their sequence ended at residue 1860 (25).…”
Section: Sites Within ␣ 1s Cytoplasmic Domains Suitable For Labeling mentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of the expression plasmids for YFPCa V 1.1, unlabeled β 1a , and unlabeled Stac3 was described previously (14,25,26). To create Stac3-BFP, the Stac3 fragment from Stac3-YFP (14) was inserted into pmTagBFP2-N1 (Addgene) using the restriction enzymes NdeI + BamHI.…”
Section: Methodsmentioning
confidence: 99%
“…En el caso del músculo esquelético, se han podido identificar sparks en anfibios, en embriones de mamífero y en miotubos en cultivo (65). Además, el empleo de la microscopía confocal de barrido láser en combinación con novedosas técnicas como la transferencia de energía por resonancia de fluorescencia (FRET) y la relación del desplazamiento del espectro de emisión/excitación (SEER) han permitido, entre otros hallazgos, estudiar el acoplamiento entre los receptores de dihidropiridinas y los de rianodina, y lograr imágenes confocales que permiten cuantificar el Ca 2+ dentro del retículo sarcoplásmico, respectivamente (66,67).…”
Section: Mediciones De Tensiónunclassified